2020
DOI: 10.1098/rspb.2019.2182
|View full text |Cite
|
Sign up to set email alerts
|

Diet contributes to urban-induced alterations in gut microbiota: experimental evidence from a wild passerine

Abstract: Urban sprawl increasingly affects the ecology of natural populations, including host–microbiota interactions, with observed differences in the gut microbiota between urban and rural hosts. While different mechanisms could explain this pattern, dietary uptake constitutes a likely candidate. To assess the contribution of diet in explaining urban–rural variation in gut microbiota, we performed an aviary experiment in which urban and rural house sparrows were fed with mimics of urban or rural diets. Before the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
96
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(110 citation statements)
references
References 66 publications
(74 reference statements)
12
96
2
Order By: Relevance
“…Anthropogenic foods contain a wider variety of macronutrients than prey 46 , particularly in the form of complex polysaccharides, and would therefore promote the higher phylogenetic diversity in the urban coyote gut that www.nature.com/scientificreports/ we observed here. These results disagree with previous studies in passerines that showed decreased microbiome diversity in urban birds 20,23 , but agree with another 22 , suggesting that how microbial diversity responds to urban habitat use may differ depending on host species, dietary components, or other aspects of an adaptation strategy. The presumed increase in dietary carbohydrates associated with an anthropogenic diet would also contribute to the abundances of the lactic acid bacteria (LAB) Streptococcus and Enterococcus, with potential implications for overall condition.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Anthropogenic foods contain a wider variety of macronutrients than prey 46 , particularly in the form of complex polysaccharides, and would therefore promote the higher phylogenetic diversity in the urban coyote gut that www.nature.com/scientificreports/ we observed here. These results disagree with previous studies in passerines that showed decreased microbiome diversity in urban birds 20,23 , but agree with another 22 , suggesting that how microbial diversity responds to urban habitat use may differ depending on host species, dietary components, or other aspects of an adaptation strategy. The presumed increase in dietary carbohydrates associated with an anthropogenic diet would also contribute to the abundances of the lactic acid bacteria (LAB) Streptococcus and Enterococcus, with potential implications for overall condition.…”
Section: Discussioncontrasting
confidence: 99%
“…Microbiome research continues to demonstrate the importance of the microbiome across diverse animal hosts in the context of environmental perturbation. Urban-induced alterations in the microbiome have been observed in wild birds [20][21][22][23] and linked to physiological stress in squirrels 24 . Disturbances related to urbanization have been shown to affect microbiome diversity and composition in several animal species [25][26][27] .…”
mentioning
confidence: 99%
“…Exploration of host-gut microbiome dynamics of wild hosts is important to better understand the exibility, resilience and long-term associations of symbiotic interactions under dietary changes. By examining the exibility and resilience of wild omnivorous passerine bird gut microbiomes through diet manipulation, our ndings document a rapid and signi cant impact of diet, aligning with other studies on passerine birds [51,52]. We observed a signi cant deviation in microbial community structure from the initial gut microbiomes after diet manipulation, but we found no signi cant differences in gut communities between the three diet groups (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Intra-speci c differences in bird populations from habitats with potentially different food availabilities further support the plastic nature of bird gut microbiomes [28,31,[45][46][47][48][49][50], as does the higher individual variation and gut bacterial diversity of omnivorous birds compared to bird species with more specialized diets (e.g., insectivores) [14]. The gap in pinpointing the impact of diet on gut microbiomes has to some extent been lled by recent diet manipulation studies of Passer domesticus (house sparrows) [51] and Parus major (great tits) [52], in which gut microbiomes respond according to dietary contents. If dietary changes are regular (e.g., seasonality and migration) we would expect gut microbiomes to cyclically change over time depending on temporal changes in food availability [24,53].…”
Section: Introductionmentioning
confidence: 99%
“…In a rapidly urbanizing world, perturbations to predator-prey relationships can drastically change human-wildlife interactions, ecosystem processes, and species extinctions, it is therefore critically important to understand these changes to inform future efforts to mitigate them. We recommend future studies aim to obtain long-term diet data at multiple sites for predatory species including at the individual level, as quantifying dietary changes over time with growing infrastructures can provide guidance on coexistence strategies for humans and wildlife (Newsome et al, 2015;Teyssier et al, 2020). The inclusion of stable isotopes in future urban-rural diet analyses would fill important information gaps to couple trophic and urban ecology, as these data capture a crucial dimension of niche space at a broader trophic level.…”
Section: Discussionmentioning
confidence: 99%